Snare-tip soft coagulation is effective and efficient as a first-line modality for treating intraprocedural bleeding during Barrett’s mucosectomy - Vosko, Sergei; Gupta, Sunil; Shahidi, Neal; Hourigan, Luke F.; van Hattem, W. Arnout; Bar-Yishay, Iddo; Schoeman, Scott; Sidhu, Mayenaaz; Burgess, Nicholas G.; Lee, Eric Y. T.; Bourke, Michael J. (Endoscopy, 2020)
Background Intraprocedural bleeding (IPB) during multiband mucosectomy (MBM) for Barrett’s neoplasia can obscure the endoscopic field. Current hemostatic devices may affect procedure continuity and technical success. Snare-tip soft coagulation (STSC) as a first-line therapy for primary hemostasis has not previously been studied in this setting. Methods Between January 2014 and November 2019, 191 consecutive patients underwent 292 MBM procedures for Barrett’s neoplasia within a prospective observational cohort in two tertiary care centers. A standard MBM technique was performed. IPB was defined as bleeding obscuring the endoscopic field that required intervention. The primary outcome was the technical success and efficacy of STSC.Results IPB occurred in 63 MBM procedures (21.6 %; 95 % confidence interval 17.3 % – 26.7 %). STSC was attempted as first-line therapy in 51 IPBs, with the remainder requiring alternate therapies because of pooling of blood. STSC achieved hemostasis in 48 cases (94.1 % by per-protocol analysis; 76.2 % by intention-to-treat analysis). No apparatus disassembly was required to perform STSC. Conclusions STSC is a safe, effective, and efficient first-line hemostatic modality for IPB during MBM for Barrett’s neoplasia.